Pengabdian Masyarakat dengan “Sosialisasi Pengaruh Penggunaan Gadget pada Anak” di Posyandu Remaja Kelurahan Banyurip - Ni'matul Ulya; Ana Setyowati; Swasti Artanti (LPPM Akbid Harapan Ibu Pekalongan, 2023)
The development of advanced technology can increase internet usage in adolescents to spend time every day using social media or the like. Gadgets have an important role in human life, as technological advances are created to make big changes from children to adults. On the other hand, gadgets have a negative or bad impact if their use is not adjusted to the actual benefits or functions. Socialization of the